(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the role, didactic possibilities, and challenges of artificial intelligence technologies in primary education. The study highlights the importance of AI in individualizing learning, developing students’ speech activity, and presenting educational content in interactive formats. It also examines the use of AI in reading lessons, including transforming stories into video formats and generating automated tasks and tests, which helps save teachers’ time. However, excessive use of AI may lead to decreased independent thinking and increased dependence on ready-made answers. The results show that the effectiveness of AI depends on its methodologically appropriate implementation in the educational process.